1994
DOI: 10.1159/000139248
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Eugenol and Ginger Oil on Arthritic Rats

Abstract: This study examined the effect of eugenol and ginger oil on severe chronic adjuvant arthritis in rats. Severe arthritis was induced in the right knee and right paw of male Sprague-Daw-ley rats by injecting 0.05 ml of a fine suspension of dead Mycobacterium tuberculosis bacilli in liquid paraffin (5 mg/ml). Eugenol (33 mg/kg) and ginger oil (33 mg/kg), given orally for 26 days, caused a significant suppression of both paw and joint swelling. These findings suggest that eugenol and ginger oil have potent antiinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 10 publications
0
65
0
3
Order By: Relevance
“…Many studies were carried out on the pungent constituents of fresh and dried ginger rhizomes. Among the pharmacological effects demonstrated are antiplatelets, antioxidant, anti-tumor, anti-rhino viral, anti-hepatotoxicity, anti-arthritic effect and anti-inflammatory [3][4][5]. The 6-Gingerol is an important active principle of plant which has been used as a marker compound for quality control and standardization of the plant and its formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were carried out on the pungent constituents of fresh and dried ginger rhizomes. Among the pharmacological effects demonstrated are antiplatelets, antioxidant, anti-tumor, anti-rhino viral, anti-hepatotoxicity, anti-arthritic effect and anti-inflammatory [3][4][5]. The 6-Gingerol is an important active principle of plant which has been used as a marker compound for quality control and standardization of the plant and its formulations.…”
Section: Introductionmentioning
confidence: 99%
“…1994;Mansuy et al, 1986), and act as hydroxyl radical scavengers (Taira et al, 1992). Because eugenol and isoeugenol inhibit arachidonic acid-induced thromboxane B2, they are extensively used as anti-in¯ammatory compounds (Naidu, 1995;Sharma et al, 1994). Besides their antiin¯ammatory property, anethole and its analogues exhibit chemopreventive activities as indicated by suppression of the incidence and multiplicity of both invasive and noninvasive adenocarcinomas (Reddy et al, 1993;Reddy, 1996Reddy, , 1997Lubert et al, 1997;AlHarbi et al, 1995).…”
mentioning
confidence: 99%
“…Studies with other plant species have been reported, such as Benencia et al (2000), who identified dosedependent immunosuppressive activity in an extract from Trichilia glabra, which displays anti-viral, antiinflammatory and anti rheumatic properties. Sharma et al (1994) detected an immunostimulatory potential in extracts from leaves of Picrorhiza kurroa, used for anti-inflammatory, anti-arthritis, gastrointestinal and urinary disorders. Tiwari et al (2004) also detected immunostimulatory activity in an aqueous extract of Tridax procumbens (used for its anti-inflammatory, antimicrobial and hepatoprotectible properties).…”
Section: Discussionmentioning
confidence: 99%